(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Excessive free cash flows can lead to high agency problems as retaining free cash flow reduces the ability of capital market to monitor managers. Managers are also likely to waste the free cash flow on value-decreasing investments. Based on the free cash flow hypothesis, this study examines the relationship between corporate governance and firm performance of a sample of high agency costs of free cash flow firms, which is defined as firms that have high free cash flow and low investment opportunities. The sample firms are extracted from firms listed on the S&P/TSX composite index between 2009 and 2012. Using corporate governance scores provided by The Globe and Mail, this study finds that better corporate governance is associated with better firm performance, measured by return on equity. The results highlight the importance of corporate governance in protecting shareholders’ interests.